2004
DOI: 10.1002/app.20594
|View full text |Cite
|
Sign up to set email alerts
|

MoO2(acac)2 immobilized on polymers as catalysts for cyclohexene epoxidation: Effect of the degree of crosslinking

Abstract: ABSTRACT:Crosslinked poly(4-vinylpyridine-co-styrene) used as support for a immobilized oxomolybdenum complex was synthesized by radical polymerization. As crosslinking agent, 1,4-divinylbenzene (DVB) was incorporated at 2, 4, and 6 mol %. Catalysts having similar MoO 2 (acac) 2 loading on different resins were obtained by refluxing a solution of the complex with the polymeric supports at 70°C. FTIR, specific surface area, and XPS techniques were used for characterization. It was found that a significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In the case of MoO 2 (acac) 2 supported on poly(4-vinylpyridine-co-styrene) [14] or polyaniline [15] metal leaching was not investigated in detail and data on the catalytic long-term performance of these catalysts are not available.…”
Section: Full Papersmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of MoO 2 (acac) 2 supported on poly(4-vinylpyridine-co-styrene) [14] or polyaniline [15] metal leaching was not investigated in detail and data on the catalytic long-term performance of these catalysts are not available.…”
Section: Full Papersmentioning
confidence: 98%
“…Highly active as well as recyclable and stable catalysts based on polybenzimidazole [12] and polyimides [13] have been reported. Recently, crosslinked poly(4-vinylpyridine-co-styrene) [14] was used as support for the immobilisation of MoO 2 (acac) 2 . Furthermore, polyaniline-supported MoO 2 (acac) 2 [15] was shown to be an active and recyclable catalyst for the oxidation of alcohols to aldehydes and ketones using molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…[65] Reaction kinetics as well as spectroscopic results, however, indicated the presence of non-paramagnetic mononuclear and polynuclear Rh carbonyl immobilised species. Also in poly(4-vinylpyridine) cross-linked with DVB it was shown that Mo(VI) of a MoO 2 A C H T U N G T R E N N U N G (acac) 2 complex was attached on the pyridine N. [66] The most active catalyst in the epoxidation of alkenes with tert-butyl hydroperoxide was obtained at an intermediate degree (4 %) of cross-linking. Crosslinked poly(4-vinylpyridine) as such could retain mononuclear Cu species and catalysed in basic medium the low temperature water gas shift reaction as well as the hydrodechlorination of chlorobenzene into benzene and biphenyl.…”
Section: Scheme 19mentioning
confidence: 98%
“…Grafting Mo compounds to functionalized polymer supports [8,9], preparation of amorphous Mo silicates via sol-gel method [10,11] and incorporation of Mo in the framework of silicalite are examples in this regard [12]. Micelle-templated inorganic oxides of silica and alumina have emerged in the past decade as very promising support materials owing to their unique textural properties (high surface area, pore volume and narrow pore size distribution) [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%